1964
DOI: 10.1037/h0045809
|View full text |Cite
|
Sign up to set email alerts
|

Rigid thinking in suicidal individuals.

Abstract: The folklore hypothesis that suicidal individuals think in a rigid manner was evaluated by the California F Scale and the Rokeach Map Test. They were administered to a suicidal attempt group, a group of psychosomatic patients, and to hospitalized normal Ss. It was found that the suicidal group earned significantly higher California F Scale scores (p < .01), and that they also shifted significantly fewer times (p < .01) on the Rokeach Map Test, when compared with the other 2 groups. It was cautiously concluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
2
2

Year Published

1968
1968
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 22 publications
(13 reference statements)
3
76
2
2
Order By: Relevance
“…Suicide attempters may not be aware of the uncertainty associated with these decks, seeing options as certain on the basis of initially-determined immediate outcomes. This "lack of flexibility" has previously been described in suicide attempters as "cognitive rigidity" (Neuringer, 1964).…”
Section: Discussionmentioning
confidence: 98%
“…Suicide attempters may not be aware of the uncertainty associated with these decks, seeing options as certain on the basis of initially-determined immediate outcomes. This "lack of flexibility" has previously been described in suicide attempters as "cognitive rigidity" (Neuringer, 1964).…”
Section: Discussionmentioning
confidence: 98%
“…Those to whom he might turn for help may also be those whom he resents. This source of conflict, when compounded with factors, such as fewer resources available, extreme rigidity in thought, and a tendency to react extremely to information from the environment (12,13), and a tendency to be emotionally disturbed, may lead inexorably to consideration of suicide and possibly to a suicide attempt.…”
Section: Journal Of Cener4l Psychologymentioning
confidence: 99%
“…There is some evidence that this may be true. Neuringer (22), working from a different point of view, has reported that on a variety of psychological tasks suicidal individuals are more rigid in their thought than are nonsuicidal individuals or psychoneurotic patients. (b) To what end does the suicidal individual extort and distort evidence?…”
Section: Suicide and Hostilitymentioning
confidence: 99%